Coordinate regulation of methanol utilization pathway genes of Komagataella phaffii by transcription factors and chromatin modifiers - Gupta, Aditi; Rangarajan, Pundi N. (Frontiers in Microbiology, 2022)
The methylotrophic yeast Komagataella phaffii (a.k.a. Pichia pastoris) harbours a methanol utilization (MUT) pathway, enabling it to utilize methanol as the sole source of carbon. The nexus between transcription factors such as Mxr1p and Trm1p and chromatin-modifying enzymes in the regulation of genes of MUT pathway has not been well studied in K. phaffii. Using comparative transcriptomics, we demonstrate that Gcn5, a histone acetyltransferase, and Gal83, one of the beta subunits of nuclear-localized SNF1 (sucrose non-fermenting 1) kinase complex are essential for the transcriptional regulation by Mxr1p and Trm1p. We conclude that interactions amongst Gcn5, Snf1, Mxr1p and Trm1p play a critical role in the transcriptional regulation of genes of MUT pathway of K. phaffii.